Ekofeminsime dalam Film Nona Kedi yang Tak Pernah Melihat Keajaiban (2013) - Farobi Fatkhurridho; Suma Riella Rusdiarti (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
The exploitation of nature and discrimination against women have similarities in unequal power relations. From an anthropocentric point of view, the exploitation of nature has relevance to the issue of feminism. It refers to the terminology of dualism hierarchy in the realm of ecofeminism. Nature and women occupy the same position, namely as objects of the oppressed. In this case, regime, capitalism, and masculinity become the dominant force that has a position as the oppressor. A Lady Caddy Who Never Saw a Hole in One (2013) is a short film that presents a form of perpetuating the issue of dualism hierarchy. The result from this research shows how a lady caddy figure becomes a symbol of the product and represents the exploitation of nature in the eviction of land for golf and luxury hotels. The patterns and symbols presented through the narrative structure and cinematographic aspects depict the relationship between capitalism, regimes, women, and nature which refer to the perpetuation of dualism hierarchy.